Social Construction of Inclusive Education as Peace Practice in Islamic Schooling - Gymnastiar, Iman Ahmad; Ambarnis, Annisaa (Kongregasi Hati Kudus Yesus (RSCJ) Indonesia, 2025)
This study aims to explain how inclusive education practices at Cendekia Muda Universal Islamic School, Bandung, West Java, contribute to building a culture of peace through the social processes formed in the daily interactions of the school community. The analysis focuses on how Islamic-based values, relationships, and school programs shape inclusive social identities, particularly for students with special needs. This research employs a qualitative approach through participant observation, in-depth interviews with the principal, teachers, and students from Grades X–XII, as well as document analysis. The findings demonstrate that peace values are constructed through inclusive routines that normalize differences, foster peer support, and reduce social distance among students. Islamic religious programs such as Friday Reflections, akhlak mentoring, and cross-identity dialogue serve as key arenas for reconstructing stereotypes, strengthening empathy, and expanding social solidarity. In addition, collaboration among the principal, teachers, the inclusion coordinator, parents, and students creates a coherent and supportive educational ecosystem that nurtures open-minded, egalitarian, and cooperative student character. This study concludes that an inclusion model grounded in Islamic values holds transformative potential for cultivating sustainable peace within schools. As its original contribution, this research proposes the concept of “inclusivity as a peace practice” within Islamic schooling—an area still rarely explored in Indonesian sociology of education.